Effect of Shading During Grain Filling on the Physicochemical Properties of Fresh Waxy Maize - Da-lei LU; Xu-li SUN; Xin WANG; Fa-bao YAN; Wei-ping LU (Journal of Integrative Agriculture, 2013)
Grain physicochemical properties determine the table quality of fresh waxy maize. Two waxy maize varieties, Suyunuo 5 (shading tolerant) and FHN003 (shading sensitive), were used to estimate the effect of shading (plants received 30% less radiation than control) during grain filling (from 0 d to 23 d after pollination) on physicochemical properties of fresh waxy maize grain. Shading decreased the grain fresh weight of Suyunuo 5 and FHN003 by 8.4 and 19.1%, respectively. Shading increased the grain water content of FHN003, whereas that of Suyunuo 5 was not affected. In both varieties for shading treatment, soluble sugar, starch and protein contents were decreased, whereas zein content was increased. The changes in globulin, albumin and glutenin contents under shading were variety dependent. In both varieties, shading decreased λmax, iodine binding capacity and the percentage of large starch granules (diameter >17 μm) but increased crystallinity. The results of rapid visco analysis showed that the viscosity characteristics (except for pasting temperature) of both varieties were decreased by shading; however, FHN003 was more severely affected than Suyunuo 5. Under shading, ΔHret and %R were decreased in both varieties, whereas the changes in ΔHgel and transition temperatures were variety dependent. Hardness, cohesiveness and chewiness were decreased in both varieties. Significant differences in physicochemical characteristics were observed between the two varieties.